HUBUNGAN DUKUNGAN KELUARGA, PENGETAHUAN, DENGAN KEAKTIFAN LANJUT USIA (Lansia) MENGIKUTI KEGIATAN POSYANDU LANSIA DI WILAYAH PUSKESMAS GADING SURABAYA - NINDY VARA MEIGIA (UNUSA Press, 2020)
Minimum Standards Service is basic service quality regulation that is entitled to be obtained by every citizen. Elderly people must obtain 100% health services. Various factors can lead to low visits to the elderly posyandu in the Gading Puskesmas area in 2017. Objective: to find out the relationship between family support, knowledge, and elderly activities in the elderly posyandu in Gading Surabaya puskesmas. Method: The type of research is observational analytic with a cross-sectional design. Data processing and analysis is done by univariate and bivariate. Data collection techniques by conducting simple random sampling with a sample of 94 elderly people. Location and time of research from December 2018 at the posyandu in the Gading Surabaya health center area. Results: There is a significant value of 0,000 <0,05, so it can be concluded is have a relationship with family support, knowledge of elderly with activity following the elderly posyandu at Gading Surabaya health center